2021
DOI: 10.3390/jcm10020289
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic and Lockdown Measures on Quality of Life among Italian General Population

Abstract: The COVID-19 pandemic that has hit the world in the year 2020 has put a strain on our ability to cope with events and revolutionized our daily habits. On 9 March, Italy was forced to lockdown to prevent the spread of the infection, with measures including the mandatory closure of schools and nonessential activities, travel restrictions, and the obligation to spend entire weeks in the same physical space. The aim of this study was to assess the impact of the COVID-19 pandemic and lockdown measures on quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
99
3
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(138 citation statements)
references
References 53 publications
20
99
3
5
Order By: Relevance
“…However, Ping et al [5] and Vu et al [29] did not nd a signi cant relationship between utility score and gender. The results of our analysis showed that unlike previous studies [5,29] and like other studies [30], education level and utility score have a direct and signi cant relationship. People with higher education are more likely to have access to a better environment (for example, in terms of pollution, access to information, and skills) and more nancial resources.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…However, Ping et al [5] and Vu et al [29] did not nd a signi cant relationship between utility score and gender. The results of our analysis showed that unlike previous studies [5,29] and like other studies [30], education level and utility score have a direct and signi cant relationship. People with higher education are more likely to have access to a better environment (for example, in terms of pollution, access to information, and skills) and more nancial resources.…”
Section: Discussioncontrasting
confidence: 83%
“…And it did not report a signi cant difference in other dimensions. In explaining their ndings, these researchers stated that since the Covid-19 situation had the greatest impact on education and the job market, and as a result delayed youth projects (marriage, nding a job, graduation), the most negative impact on health was imposed to the youth [30].…”
Section: Discussionmentioning
confidence: 99%
“…A lower level of education was associated with perceived threat from COVID-19, perhaps related to access to sources of information and to understanding based on previous knowledge [47,48,50]. Thus, a higher level of education would be associated with a greater critical capacity of information consumed and processed and the tendency to seek other sources of information to corroborate or refute information acquired [51].…”
Section: Discussionmentioning
confidence: 98%
“…Now nearly a year into its impact, COVID-19 has been having a tremendous impact on the quality of life for the Italian population. The nature of individual experience of the pandemic for Italians has varied depending in part on sociodemographic factors, with women and those with previously diagnosed medical conditions bearing a particularly intense burden (Epifanio et al, 2021). The mental state of the Italian population has been severely tested, and multiple studies have found a marked increase in psychological symptoms in the nonclinical population.…”
Section: Introductionmentioning
confidence: 99%